Exploring train driving automation and signaling interaction - Patrick Urassa (Transportation Engineering, 2025)
The push for better capacity utilization, punctuality, passenger comfort, and energy efficiency has accelerated the adoption of more automated trains. Concurrently, advancements in signaling systems to enhance safety and the European Union's efforts to establish a unified signaling system are becoming more evident. These technologies, although distinct, have the potential to complement each other, with automation handling the operational aspects of train driving while signaling systems oversee signaling functionalities. This study aims to investigate the interaction between train automation and signaling systems. This exploration was motivated by the observation that signaling systems may have been developed based on driver-based approaches; however, more advanced automated systems now require minimal or no human involvement. The study seeks to answer the research questions: How has research on the interaction between train-driving technologies and signaling systems developed over time? And what gaps exist in their interaction? To achieve this, a scoping study was conducted, and 75 peer-reviewed articles were included to explore the interaction of automation and signaling systems. The findings of this study indicate a versatile body of literature and a significant rise in research activity starting around 2015. The study reveals the need for specific operational adaptations to achieve higher levels of automation in advanced signaling environments. Furthermore, the identified research opportunities provide a foundation for future exploration and development in railway technologies overall. The study is done in connection to the Europe’s Rail FutuRe research project (FP6).